2022
DOI: 10.51454/jet.v3i1.138
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception in Learning English through Blended Learning

Abstract: Mobile technology plays an equal role with face-to-face interaction in the learning process in this current era. One of the most commonly utilized technologies is the use of social media integrated with the face-to-face teaching and learning as called a blended-learning. This recent study aims: (1) to investigate how the blended learning process is operated, (2) to determine students’ perceptions in learning English through blended learning. This study was an explanatory mixed-method research design using obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The type of questionnaire is a close-ended question containing 35 items divided into 4 aspects (behavioral, cognitive, emotional, and economic). This questionnaire was adapted and modified from that of Trowler (2010), Maulina et al (2022), Talis, Akib, & Baso (2018). To measure the data, the researchers used the Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…The type of questionnaire is a close-ended question containing 35 items divided into 4 aspects (behavioral, cognitive, emotional, and economic). This questionnaire was adapted and modified from that of Trowler (2010), Maulina et al (2022), Talis, Akib, & Baso (2018). To measure the data, the researchers used the Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini sejalan dengan sebuah sebuah pendapat yang menjelaskan pembelajaran multimedia adalah pembelajaran yang mengkombinasikan berbagai media seperti tulisan, foto/gambar, video, dan lain-lain yang digunakan sebagai alat bantu pembelajaran bagi peserta didik dalam mencapai tujuan yang diharapkan (Hamid et al, 2020). Dengan pengintegrasian multimedia interaktif ke dalam smartphone berbasis android maka sangat diharapkan hal ini dapat mendorong peserta didik agar lebih mengoptimalkan penggunaan smartphone mereka untuk kepentingan ke arah yang jauh lebih positif yaitu pembelajaran (Maulina et al, 2022).…”
Section: Pendahuluanunclassified
“…This research is different from previous studies, two previous studies focused on direct speech and indirect speech research in novels. While in this study, the researchers focus on the analysis of contrastive, that is to contrast the types of indirect speech in English and Java language and to determine whether there are similarities and differences in the form or indirect speech types of the two languages (Maulina et al, 2022). Thus this research is still important to do by looking at the example above, the researchers found the difference between saying no directly in English and Javanese, namely in the use of the word form to be and auxiliary verbs.…”
Section: Indirect Speechmentioning
confidence: 99%